2021
DOI: 10.1002/app.51827
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and the barrier characterization of the cellulose nanofibers/organic montmorillonite/poly lactic acid nanocomposites

Abstract: The hydrophobic modification of cellulose nanofibers (CNF) was carried out via free radical polymerization using methyl methacrylate (MMA) as the monomer to improve the compatibility between CNF and poly lactic acid (PLA). Followed by the preparation of the novel nanocomposites in combination of the organic montmorillonite and the substrate. The resulting nanocomposites were then coated on paper surface using a cast‐coating process in an attempt to improve the barrier properties towards water vapor and oxygen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The testing specimen was sprayed with a thin layer of gold, and then tested under a voltage of 5 kV. 19 The thermal stability of the film products was measured using a synchronous thermal analyzer (Jupiter STA 449F3, Netzsch, Selb, Germany) under a nitrogen atmosphere. During the The samples were cut by the standard cutters.…”
Section: Characterizationmentioning
confidence: 99%
“…The testing specimen was sprayed with a thin layer of gold, and then tested under a voltage of 5 kV. 19 The thermal stability of the film products was measured using a synchronous thermal analyzer (Jupiter STA 449F3, Netzsch, Selb, Germany) under a nitrogen atmosphere. During the The samples were cut by the standard cutters.…”
Section: Characterizationmentioning
confidence: 99%
“…In view of the above excellent performance, MMT is often used in the field of composite materials to improve the mechanical properties, barrier properties, and thermal stability, adsorption performance, etc. (Jiang et al 2021;Li and Zhang et al 2022). Research has shown that MMT could be uniformly dispersed in nanocellulose networks at a nanoscale to form intercalation structures, and the effective modulus of nanocomposites could reach up to 129.9 GPa (Xu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Surface modification of CNF or combination with other inorganic nanomaterials for construction of composites can potentially make up these problems, but these approaches are usually complex, and could compromise the biocompatibility or biodegradable of CNF. [9][10][11][12] Therefore, it is still a challenging task to fabricate multifunctional CNF composites with good properties while maintain the intrinsic advantages of CNF.…”
mentioning
confidence: 99%